Employee’s performance appraisal and job satisfaction at al Islam specialist hospital, Kampung Baru, Kuala Lumpur / Mohammad Firdaus Mohamad, Nurul Nailah Osman and Farah Zulkifli - Mohamad, Mohammad Firdaus; Osman, Nurul Nailah; Zulkifli, Farah (2013)
This research examined the implementation of Islamic based appraisal attributes to determine whether this system have significant impact on employee job satisfaction. The research focused on operating staff which consist of 82% of overall 222 numbers of employees in Al- Islam Specialist Hospital (AISH). The increasing numbers of employees’ turnover starting from 2010 until 2012 basically resulted by the introduction of new employee appraisal system. This research takes a mixed method of qualitative and quantitative approach in collecting the primary data. Interview with the directors and head of human resource and finance department of AISH conducted to obtain a firm level study, 140 questionnaires were distributed and 81 sets were valid to be processed. Secondary data acquired from human resource and finance department analyzed to ensure precise data and information for interpretation. The research finding showed there is a significant impact on appraisal system attributes of discipline and appearance and friendliness to the employees job satisfaction. This research ends with recommendation based on theory of fishbone, Hertzberg two factor theory and Maslow’s hierarchy of needs and concept of management discussed to provide ideas and room for improvement to Al-Islam Specialist Hospital in future.